Fear and stress regarding COVID-19 among nursing students in Universiti Sains Malaysia - Salleh, Nor Suriani Husni (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
COVID-19 has resulted in a rise in mortality cases and has created a global fear and stress among nursing students who are more susceptible to being infected by the virus. This study aimed to determine the fear and stress regarding COVID-19 among nursing students at Universiti Sains Malaysia (USM). A cross-sectional survey was conducted among 125 undergraduate nursing students from USM and recruited using a simple random sampling approach. An online survey questionnaire collected data on participants’ sociodemographic characteristics, fear, and stress of COVID-19. The nursing students' mean age (±SD) was 22.51(±3.378) years, and 88.8% were female. More than half of the students reported moderate (66.4%) and high (28.8 %) fear. Findings show that 51.2% had a moderate stress level, and 12% had a high level of stress of COVID-19. Gender and ethnicity were significantly associated with fear and stress (p<0.05). In addition, a correlation was found between fear and stress regarding COVID-19. This study concludes that fear and stress are present among nursing students. Therefore, we propose mental health support is imperative to overcome the fear and stress among nursing students caused by the pandemic.